Hydroxychloroquine in systemic lupus erythematosus (SLE). Issue 3 (4th March 2017) - Ponticelli, C.; Moroni, G.
ABSTRACT: Introduction : Hydroxychloroquine (HCQ) is an alkalinizing lysosomatropic drug that accumulates in lysosomes where it inhibits some important functions by increasing the pH. HCQ has proved to be effective in a number of autoimmune diseases including systemic lupus erythematosus (SLE). Areas covered : In this review the mechanisms of action, the efficacy, and the safety of HCQ in the management of patients with SLE have been reviewed. HCQ may reduce the risk of flares, allow the reduction of the dosage of steroids, reduce organ damage, and prevent the thrombotic effects of anti-phospholipid antibodies. The drug is generally safe and may be prescribed to pregnant women. However, some cautions are needed to prevent retinopathy, a rare but serious complication of the prolonged use of HCQ. Expert opinion : HCQ may offer several advantages not only in patients with mild SLE but can also exert important beneficial effects in lupus patients with organ involvement and in pregnant women. The drug has a low cost and few side effects. These characteristics should encourage a larger use of HCQ, also in lupus patients with organ involvement.